(untitled) (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2024)
This article examines the lexical-semantic features of mining terms in English and Uzbek languages. Mining terminology plays a crucial role in effectively communicating within the mining industry, encompassing a wide range of technical, environmental, economic, and social aspects. The study explores the specialized vocabulary used to describe mineral exploration, geology, mineral classification, mining workforce, safety procedures, economic considerations, and local mining practices. Additionally, it explores the evolving nature of mining terminology, reflecting advancements in technology, environmental concerns, and industry standards. The analysis contributes to a better understanding of the linguistic nuances and specialized language used in the mining sector.